The Impact of Mother’s Bargaining Power on the Nutritional Status of Children in Indonesia - Ahmad Yeyen Fidyani; I Dewa Gede Karma Wisana (Institute for Economic and Social Research, 2021)
Poor nutritional status, especially during childhood, has a negative impact on one’s early life as well as throughout their life. One of the factors that influences the improvement of children’s nutritional status is the bargaining power of the mother. Previous studies have limitations in that they often use cross-sectional data and indirect approaches to measuring bargaining power. This study aims to measure the impact of maternal bargaining power on children’s nutritional status in Indonesia. The unit of analysis is children aged 7–19 years (IFLS5) who still have and live with their parents (IFLS4). Using the OLS estimation method, the results show that maternal bargaining power significantly and positively influences the nutritional status of children (HA z-score).